Factor influencing women with learning disabilities deciding to, and accessing, cervical and breast cancer screening: Findings from a Q methodology study of women with learning disabilities, family and paid carers. (12th September 2022) - Sykes, Kate; McGeechan, Grant J.; Crawford, Hannah; Giles, Emma L.
Abstract: Objectives: To understand knowledge of, attitudes towards and decision‐making around cervical and breast cancer screening in women with learning disabilities, family carers and paid carers. Methods: A Q methodology study involving 13 women with learning disabilities, three family carers and five paid care workers, from the North‐East of England. A Q‐sort of 28 statements was completed with all participants completing a post‐Q‐sort interview to understand the reason behind the card placements. Factor analysis was completed using PQMethod and interpreted using framework analysis. Results: Factor 1, named 'Personal choice and ownership', explores how women with learning disabilities want to be supported to make their own decision to attend cancer screening and explored their preferred support needs. Factor 2, named 'Protecting vs. enablement', portrayed the battle family carers and paid care workers felt to protect women with learning disabilities from harm, whilst feeling that they were supporting women with learning disabilities to decide to attend cancer screening. Eight consensus statements were identified indicating a shared perspective. Conclusions: Cancer screening services should ensure that women with learning disabilities are supported to make informed decisions to attend cancer screening and then be further supported throughout the cancer pathway.